Smart Calculator 5.0 / Yusrina Andu ... [et al.]. - Andu, Yusrina; Mohamed, Nadiah; Othman, Norlida; Ahmad, Siti Noor Dina; Jaafar, Zuraida; Mohd Ruslan, Siti Zaharah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Smart Calculator 5.0 program is intended to support the first semester pre-diploma and diploma students of different backgrounds in using their calculator smartly to solve mathematics questions. Through the activities that were carried out, students are able to gain extra understanding regarding the usage of their scientific calculator. Furthermore, this program is a platform for them to be better prepared to tackle their upcoming quizzes, mid-terms, and final exams. The Smart Calculator 5.0 program was designed and conducted to support students in using scientific calculator. Participant of students are specifically those enrolled in courses such as MAT013, MAT037, MAT083, MAT133, and MAT112 comprising of Pre-Science, STEM C, Pre-Islamic Studies, and Diploma programs in UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah. A total of 195 students attended this program which was held on November 2, 2024, via the Google Meet platform, aiming to equip students with a deeper understanding of how to effectively use scientific calculators, an essential tool in their academic journey, especially in mathematics and calculus-related courses.